Adherence to a plant-based diet in relation to adipose tissue volumes and liver fat content. Issue 2 (26th May 2020) - Ratjen, Ilka; Morze, Jakub; Enderle, Janna; Both, Marcus; Borggrefe, Jan; Müller, Hans-Peter; Kassubek, Jan; Koch, Manja; Lieb, Wolfgang
ABSTRACT: Background: Better adherence to plant-based diets has been linked to lower risk of metabolic diseases but the effect on abdominal fat distribution and liver fat content is unclear. Objectives: We aimed to examine the association between different plant-based diet indices and measures of abdominal fat distribution and liver fat content. Methods: In a population-based sample of 578 individuals from Northern Germany (57% male, median age 62 y), diet was assessed with a validated FFQ and an overall, a healthy, and an unhealthy plant-based diet index were derived. Participants underwent MRI to assess volumes of visceral and subcutaneous abdominal adipose tissue and liver signal intensity (LSI), a measure of liver fat content. Fatty liver disease (FLD) was defined as log LSI ≥3.0. Cross-sectional associations of the plant-based diet indices with visceral and subcutaneous abdominal fat volumes, LSI, and FLD were assessed in linear and logistic regression analyses. The most comprehensive model adjusted for age, sex, education, smoking, alcohol, physical activity, energy intake, diabetes, hyperlipidemia, and BMI. Results: Higher overall and healthy plant-based diet indices both revealed statistically significant associations with lower visceral and subcutaneous abdominal adipose tissue volumes and with lower odds of FLD in multivariable-adjusted models without BMI. Upon additional adjustment for BMI, only the association of the healthy plant-based diet with visceral adipose tissue remained statistically significant (per 10-point higher healthy plant-based diet index, percentage change in visceral adipose tissue: −4.9%, 95% CI: −8.6%, −2.0%). None of the plant-based diet indices was associated with LSI. The unhealthy plant-based diet index was unrelated to any of the abdominal or liver fat parameters. Conclusions: Adherence to healthy plant-based diets was associated with lower visceral adipose tissue. None of the other examined associations remained statistically significant after adjustment for BMI.